2020
DOI: 10.36227/techrxiv.11419221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-Phase Distribution Locational Marginal Pricing to Manage Unbalanced Variable Renewable Energy

Abstract: This paper investigates three-phase, component-wise real and reactive distribution locational marginal pricing (DLMP). Through the use of case studies, mixtures of positive and negative, as well as real and reactive, DLMP components are explored in detail. A modified three-phase unbalanced 69-node PG&E system is used to demonstrate the validity of the three-phase real and reactive DLMP model. Results emphasize the importance of three-phase pricing schemes and reactive power pricing. The results also indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Studies on multi-phase DLMPs have recently gained popularity although the extension of DLMPs from single-phase to three-phase is not straightforward. The importance of three-phase schemes was emphasized in [30], in which it is suggested that DLMPs could be useful in power balancing across phases. In [31], a convexified OPF problem was solved to derive DLMPs for a three-phase distribution network.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on multi-phase DLMPs have recently gained popularity although the extension of DLMPs from single-phase to three-phase is not straightforward. The importance of three-phase schemes was emphasized in [30], in which it is suggested that DLMPs could be useful in power balancing across phases. In [31], a convexified OPF problem was solved to derive DLMPs for a three-phase distribution network.…”
Section: Literature Surveymentioning
confidence: 99%
“…Cost = P P RL × g P RL η P RL (30) where P P RL is the load output, g P RL is the cost to supply the PRL and η P RL is the efficiency of the load.…”
Section: B Load Modelingmentioning
confidence: 99%